The philosopher's "I" : autobiography and the search for the self - Wright, J. Lenore, 1972- (State University of New York Press, 2006)
"This book examines philosophers' autobiographies as a genre of philosophical writing. Author J. Lenore Wright focuses her attention on five philosophical autobiographies: Augustine's Confessions, Descartes' Meditations, Rousseau's The Confessions, Nietzsche's Ecce Homo, and Hazel Barnes's The Story I Tell Myself. In the context of first-person narration, she shows how the philosophers in question turn their attention inward and unleash their analytical rigor on themselves."--Jacket